Cover Feature: Organocatalytic Stereoselective Epoxidation of α‐alkylidene Oxindoles Using α, α‐diphenylprolinol in Liposome Membrane (ChemCatChem 3/2019). Issue 3 (29th January 2019) - Gasperi, Tecla; Tortora, Carola; Miceli, Martina; Steiniger, Frank; Walde, Peter; Stano, Pasquale
Abstract : The Cover Feature shows a closer look at the organocatalytic stereoselective epoxidation of α‐alkylidene oxindoles using α, α‐diphenylprolinol in a liposome membrane. In their Communication, T. Gasperi et al. demonstrate the use of the membrane of 1‐palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phosphocholine (POPC) liposomes suspended in water as a microenvironment for carrying out the organocatalytic epoxidation of an α‐alkylidene oxindole. The reaction proceeds smoothly and displays diastereo‐ and enantio‐selectivity that differs from what is achieved under bulk solution conditions. The potential of organocatalytic approaches for synthetic trans‐formations in aqueous phase in the presence of dispersed membranes is briefly discussed. More information can be found in the Communication by T. Gasperi et al. on page 973 in Issue 3, 2019 (DOI: 10.1002/cctc.201801677 ).